InsectDisease: programmatic access to the Ecological Database of the World's Insect Pathogens. Issue 12 (21st October 2022) - Dallas, Tad A.; J. Carlson, Colin; Stephens, Patrick R.; Ryan, Sadie J.; Onstad, David W.
Abstract : Curated databases of species interactions are instrumental to exploring and understanding the spatial distribution of species and their biotic interactions. In the process of conducting such projects, data development and curation efforts may give rise to a data product with utility beyond the scope of the original work, but which becomes inaccessible over time. Data describing insect host–pathogen interactions are fairly rare, and should thus be preserved and curated with appropriate metadata. Here, we introduce the insectDisease R package, a mechanism for curating, updating and distributing data from the Ecological Database of the World's Insect Pathogens, a database of insect host–pathogen associations, including attempted inoculations and infection outcomes for insect hosts and pathogens (bacteria, fungi, nematodes, protozoans and viruses). This dataset has been utilized for several projects since its inception, but without a well‐defined, curated and permanent repository, its existence and access have been limited to word‐of‐mouth connections. The current effort presented here aims to provide a means to preserve, augment and disseminate the database in a documented and versioned format. This project is an example of the type of effort that will be necessary to maintain valuable databases after the original funding disappears.